STOP!: a randomised, double-blind, placebo-controlled study of the efficacy and safety of methoxyflurane for the treatment of acute pain. Issue 8 (17th April 2014) - Coffey, Frank; Wright, John; Hartshorn, Stuart; Hunt, Paul; Locker, Thomas; Mirza, Kazim; Dissmann, Patrick
Abstract : Objective: To evaluate the short-term efficacy and safety of methoxyflurane for the treatment of acute pain in patients presenting to an emergency department (ED) with minor trauma. Methods: STOP! was a randomised, double-blind, multicentre, placebo-controlled study conducted at six sites in the UK. A total of 300 patients, 90 of whom were adolescent patients (age 12–17 years), were randomised 150:150 to receive either methoxyflurane via a Penthrox inhaler or placebo. The primary end point of the study was the change in pain intensity as measured using the visual analogue scale (VAS) from baseline to 5, 10, 15 and 20 min after the start of study drug inhalation. Patients were supplied with one inhaler containing 3 mL methoxyflurane or 5 mL placebo after enrolment and initial assessments. Age group (adolescent/adult) and baseline VAS score were controlled for in the statistical analyses. Results: A total of 149 patients received methoxyflurane, and 149 patients received placebo. Demographic and baseline characteristics were comparable between the groups. Methoxyflurane reduced pain severity significantly more than placebo (p<0.0001) at all time points tested, with the greatest estimated treatment effect of −18.5 mm (adjusted change from baseline) seen at 15 min after the start of treatment. Methoxyflurane was well tolerated, with the majority of adverse reactions being mild, transient and in line with anticipated pharmacological action. Conclusion: The results of this study suggest that methoxyflurane administered via the Penthrox inhaler is an efficacious, safe, and rapidly acting analgesic. Trial registration number: NCT01420159.